Incidence of Reproductive Disorders in Different animals treated in Teaching Hospital related to Veterinary College of Mosul University: Retrospective data (NTU Journal of Agriculture and Veterinary Science, 2025)
The current analysis was conducted to quantify the incidence of reproductive disorders in different animals examined and treated at the University Veterinary Hospital, University of Mosul. Such analysis is important in evaluating the hands-on experiences that the local veterinary students obtain in this hospital. For this analysis, data related to the animals examined and treated between January 2018 and December 2022 was retrieved from the records of the Theriogenology section and compiled in Microsoft Excel 2010. A total of 385 Pregnancy diagnosis cases were received, which represented about 50% of all cases received at the hospital. Cows represented 64% of animals received for pregnancy diagnosis. Dystocia in ewes, metritis/endometritis, retained fetal membranes, and inactive ovaries in cows, constituted the most frequent obstetrical cases received at the hospital. In general, all practical reproductive disorders in different she-animals like mare, cow, ewe, nanny goat, buffalo, cat, and bitches were recorded in this analysis which in our point of view add many information in way to improve undergraduate student’s skills.   In conclusion, improving skills in pregnancy diagnosis, treatment of dystocia and retained fetal membranes, and diagnosis of metritis/endometritis and inactive ovaries should be considered in the training of local students and it's important to direct and focus practical training and treatment to in the way to deal with reproductive disorders which may related to new situations and conditions like global warming and using best equipment for teaching.